2016
DOI: 10.1111/bjd.14357
|View full text |Cite
|
Sign up to set email alerts
|

Airborne formaldehyde causes skin barrier dysfunction in atopic dermatitis

Abstract: Short-term exposure to formaldehyde causes skin barrier dysfunction in both healthy children and children with AD, and this effect is more prominent in children with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 21 publications
0
33
0
2
Order By: Relevance
“…The higher incidence of infantile eczema observed under urban environmental conditions may be result of complex mechanism which may include direct harmful effects on infantile skin. In this connection, attention is drawn to detrimental role of formaldehyde the short‐term exposure of which increased transepidermal water loss in both healthy children and children with AD . It also was shown that environmental exposures to tobacco smoke or VOCs positively associated with levels of circulating eosinophil/basophil progenitors in children at 1 year of age .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher incidence of infantile eczema observed under urban environmental conditions may be result of complex mechanism which may include direct harmful effects on infantile skin. In this connection, attention is drawn to detrimental role of formaldehyde the short‐term exposure of which increased transepidermal water loss in both healthy children and children with AD . It also was shown that environmental exposures to tobacco smoke or VOCs positively associated with levels of circulating eosinophil/basophil progenitors in children at 1 year of age .…”
Section: Discussionmentioning
confidence: 99%
“…In this connection, attention is drawn to detrimental role of formaldehyde the short-term exposure of which increased transepidermal water loss in both healthy children and children with AD. 20 It also was shown that environmental exposures to tobacco smoke or VOCs positively associated with levels of circulating eosinophil/basophil progenitors in children at 1 year of age. 21 It still remains to be elucidated the AD mechanisms related to triggering or aggravating of allergic or inflammatory processes in early childhood after exposure to air pollutants.…”
Section: Air Pollutantsmentioning
confidence: 97%
“…Although the exact pathogenesis of AD remains unknown, birth cohort studies have suggested that air pollutants such as PM, NO 2 or phthalate may play an important role in AD development . Air pollutants have also been revealed to contribute to the aggravating of pre‐existing AD . In addition, studies of biological mechanism suggested that dust particles and diesel exhaust particulates can exert toxicological effects on human skin …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Air pollutants have also been revealed to contribute to the aggravating of pre-existing AD. 12,13 In addition, studies of biological mechanism suggested that dust particles and diesel exhaust particulates can exert toxicological effects on human skin. 14 Meteorological factors such as temperature and relative humidity have also been suggested to affect the prevalence and severity of AD and should be considered in the management of AD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its distinct, pungent smell and color-altering properties, formalin has been classified as an occupational hazard for health personnel. It has been reported to cause contact dermatitis, upper airway inflammation, asthma, and is implicated in nasopharyngeal cancer, sinonasal cancer, and lymphohematopoietic cancer (Nelson et al, 1986;Raja & Sultana, 2012;Friis et al, 2014;Pontén & Bruze, 2015;Davies, 2016;Kim et al, 2016). Over the past 100 years, various substances have been reported as being used preservation of the cadaveric tissue.…”
Section: Introductionmentioning
confidence: 99%